Cholesterol in viral envelope determines infectivity of SARS-CoV-2 and other coronaviruses - Xu, Xiaoying; Wang, Xueyan; Zhang, Xiafeng; Jin, Xin; Tan, Yun; Huang, Lin; Zhou, Mingqian; Wen, Chengping (Frontiers in Microbiology, 2025)
The SARS-CoV-2 pandemic had unprecedented impacts on public health and the economy. Many studies have focused on the mechanisms of SARS-CoV-2 entry into host cells, particularly the spike (S) protein mediated receptor engagement and subsequent virus-host membrane fusion dynamics. However, the mechanistic contribution of cholesterol within spike-incorporated viral envelopes to infectivity has not been well characterized. Herein, we show that targeted cholesterol depletion from the viral envelopes of SARS-CoV-2, SARS-CoV, and MERS-CoV directly impaired viral infectivity in a dose-dependent manner. Although modulation of host cell membrane cholesterol exerted relatively minor effects on viral entry, host cellular cholesterol homeostasis critically governs progeny virion infectivity by determining cholesterol content within nascent viral envelopes. Virions derived from cells with reduced plasma membrane cholesterol demonstrate significantly attenuated infectivity in SARS-CoV-2 and related coronaviruses. In addition, we detected that exogenous cholesterol replenishment restored SARS-CoV-2 entry efficiency by augmenting virus attachment. Collectively, our data demonstrate that biophysical properties of human coronavirus envelopes, particularly cholesterol stoichiometry, function as a key molecular determinant regulating host cell susceptibility. These findings position viral lipidome remodeling as a viable therapeutic target for developing host-directed broad-spectrum antivirals.